The Effect of Neurodiversity on State Defense and Cybersecurity - Asrudin, Muhammad; Perwita, Anak Agung Banyu; Purwantoro, Susilo Adi; Praditya, Editha; Almubaroq, Hikmat Zakky; Hananto, Subarkah (CV. AFDIFAL MAJU BERKAH, 2024)
Neurodiversity is as much a part of human diversity as cultural or gender diversity. This perspective counters the traditional view of neurological conditions as deficits, and encourages recognition of the unique strengths of those with these conditions. The research method used is the critical analysis method. This method not only focuses on collecting empirical data, but also emphasizes a better understanding of the social, cultural and historical context. Neurodiversity encompasses a wide range of individuals with conditions such as autism and dyslexia. The main focus is to capitalize on their unique strengths. An inclusive design approach is essential to optimize the talents that individuals bring to the team. By implementing a strategic approach that supports the strengths of diverse team members, organizations can increase innovation and create an inclusive work environment. Workers with a diversity of intelligences report increased confidence when their job responsibilities match their skills and strengths. In addition, increasing understanding of neurodiversity in the workplace helps all staff members to better understand and appreciate neurodiverse coworkers, thereby increasing cooperation and morale. The cognitive diversity possessed by neurodiverse teams can increase productivity and innovation, which is particularly important in sectors such as state defense and cybersecurity.